Adequacy of nutrient intakes in elite junior basketball players - Nikic, M.; Pedisic, Z.; Satalic, Z.; Jakovljevic, S.; Venus, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The aim of this study was to assess the nutrient intakes of elite junior basketball players in comparison with nonathletes. Methods: A previously designed food frequency questionnaire was undertaken by 57 male elite junior basketball players 15 to 16 years of age and 53 nonathlete peers. Results: Mean estimated energy intake was more than 700 kcal higher in basketball players than in the nonathletes (p = .002). In both groups estimated energy intake was ~14% from protein, 38% from fat, and ~48% from carbohydrates. For the basketball players, estimated protein intake was below 1.4 g/kg in 32% of the group and above 1.7 g/ kg in 51%, while carbohydrate intake was below 6 g/kg in 56%. Percentages of participants who apparently failed to meet the estimated average requirement for micronutrients were higher in the nonathlete group. The nutrients most likely to fail to meet the recommendations for nutrient density were vitamin A (~70%), zinc (49% in basketball players and 30% in nonathletes), niacin and calcium (~30% for both micronutrients in both groups). Conclusion: Within the limitations of the survey methodology, elite junior basketball players appear to consume higher absolute energy, macronutrient and micronutrient intakes than nonathletes, but the contribution of macronutrients to daily energy intake and the nutrient density of food choices was similar for both groups. Elite junior basketball players might benefit from nutrition education targeting carbohydrate and protein intake. Dietary modifications that increase intakes of vitamin A, zinc, calcium and niacin in the diets of both groups might also be of value.